Soil-transmitted helminth infections in free-ranging non-human primates from Cameroon and Gabon - Sirima, C; Bizet, C; Hamou, H; Červená, B; Lemarcis, T; Esteban, A; Peeters, M; Mpoudi Ngole, E; Mombo, I M; Liégeois, F; Petrželková, K J; Boussinesq, M; et al. (Parasites & vectors, 2021)
BACKGROUND: Zoonotic diseases are a serious threat to both public health and animal conservation. Most non-human primates (NHP) are facing the threat of forest loss and fragmentation and are increasingly living in closer spatial proximity to humans. Humans are infected with soil-transmitted helminths (STH) at a high prevalence, and bidirectional infection with NHP has been observed. The aim of this study was to determine the prevalence, genetic diversity, distribution and presence of co-infections of STH in free-ranging gorillas, chimpanzees and other NHP species, and to determine the potential role of these NHP as reservoir hosts contributing to the environmental sustenance of zoonotic nematode infections in forested areas of Cameroon and Gabon. METHODS: A total of 315 faecal samples from six species of NHPs were analysed. We performed PCR amplification, sequencing and maximum likelihood analysis of DNA fragments of the internal transcribed spacer 2 (ITS2) nuclear ribosomal DNA to detect the presence and determine the genetic diversity of Oesophagostomum spp., Necator spp. and Trichuris spp., and of targeted DNA fragments of the internal transcribed spacer 1 (ITS1) to detect the presence of Ascaris spp. RESULTS: Necator spp. infections were most common in gorillas (35 of 65 individuals), but also present in chimpanzees (100 of 222 individuals) and in one of four samples from greater spot-nosed monkeys. These clustered with previously described type II and III Necator spp. Gorillas were also the most infected NHP with Oesophagostomum (51/65 individuals), followed by chimpanzees (157/222 individuals), mandrills (8/12 samples) and mangabeys (7/12 samples), with O. stephanostomum being the most prevalent species. Oesophagostomum bifurcum was detected in chimpanzees and a red-capped mangabey, and a non-classified Oesophagostomum species was detected in a mandrill and a red-capped mangabey. In addition, Ternidens deminutus was detected in samples from one chimpanzee and three greater spot-nosed monkeys. A significant relative overabundance of co-infections with Necator and Oesophagostomum was observed in chimpanzees and gorillas. Trichuris sp. was detected at low prevalence in a gorilla, a chimpanzee and a greater spot-nosed monkey. No Ascaris was observed in any of the samples analysed. CONCLUSIONS: Our results on STH prevalence and genetic diversity in NHP from Cameroon and Gabon corroborate those obtained from other wild NHP populations in other African countries. Future research should focus on better identifying, at a molecular level, the species of Necator and Oesophagostomum infecting NHP and determining how human populations may be affected by increased proximity resulting from encroachment into sylvatic STH reservoir habitats.
Keywords: divoká zvířata; feces; Helminthiasis, Animal; DNA helmintů; Phylogeny; Gabon; helmintózy zvířat; Kamerun; Faeces; Female; půda; Cameroon; primáti; zoonózy; DNA, Helminth; zvířata; Zoonosis; Animals, Wild; Feces; cizopasní červi; Africa; Non-human primate; Helminths; ženské pohlaví; Male; Zoonoses; Animals; Soil; mužské pohlaví; Primates; Soil-transmitted helminths